A new framework to map fine resolution cropping intensity across the globe: Algorithm, validation, and implication - Liu, Chong; Zhang, Qi; Tao, Shiqi; Qi, Jiaguo; Ding, Mingjun; Guan, Qihui; Wu, Bingfang; Zhang, Miao; Nabil, Mohsen; Tian, Fuyou; Zeng, Hongwei; Zhang, Ning; et al. (Remote sensing of environment, 2020)
Accurate estimation of cropping intensity (CI), an indicator of food production, is well aligned with the ongoing efforts to achieve sustainable development goals (SDGs) under diminishing natural resources. The advancement in satellite remote sensing provides unprecedented opportunities for capturing CI information in a spatially continuous manner. However, challenges remain due to the lack of generalizable algorithms for accurately and efficiently mapping global CI with a fine spatial resolution. In this study, we developed a 30-m planetary-scale CI mapping framework with the reconstructed time series of Normalized Difference Vegetation Index (NDVI) from multiple satellite images. Using a binary crop phenophase profile indicating growing and non-growing periods, we estimated pixel-by-pixel CI by enumerating the total number of valid cropping cycles during the study years. Based on the Google Earth Engine cloud computing platform, we implemented the framework to estimate CI during 2016–2018 in eight geographic regions across continents that are representative of global cropping system diversity. Comparison with PhenoCam network data in four cropland sites suggests that the proposed framework is capable of capturing the seasonal dynamics of cropping practices. Spatially, overall accuracies based on validation samples range from 80.0% to 98.9% across different regions worldwide. Regarding the CI classes, single cropping systems are associated with more robust and less biased estimations than multiple cropping systems. Finally, our CI estimates reveal high agreement with two widely used land surface phenology products, including Vegetation Index and Phenology V004 (VIP4) and Moderate Resolution Imaging Spectroradiometer Land Cover Dynamics (MCD12Q2), meanwhile providing much more spatial details. Due to its robustness, the developed CI framework can be potentially generalized to produce global fine resolution CI products for food security and other applications. •A new framework is proposed for cropping intensity mapping at fine resolution.•Cropping intensity is determined by a binary phenophase profile for each cropland pixel.•The framework can be applied to various agro-ecological conditions.•Overall accuracies range 80.0%–98.9% based on results from eight regions across the globe.